2015
DOI: 10.1017/s0144686x15000999
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness among older people as a social problem: the perspectives of medicine, religion and economy

Abstract: This article offers a theoretical framework for studying loneliness among the elderly from a social problems perspective. The framework is a combination of the constructionist approach to social problems by Spector and Kitsuse and the theory of social systems by Luhmann. With the first we understand the social problem of loneliness among the elderly as the result of claims-making activities by different key actors. These activities are guided by cultural themes, images and causality constructions. With the sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Thus, loneliness is constructed as an evolutionary issue and social relations are presented as a crucial part of human existence. The report is, therefore, not a type of societal diagnosis where developments in modern society alone are seen as generating loneliness (Schirmer and Michailakis, 2016). Regarding the issue of responsibility, elder-care is seen as focusing on all other factors affecting humans and not focusing on the social needs of older people.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, loneliness is constructed as an evolutionary issue and social relations are presented as a crucial part of human existence. The report is, therefore, not a type of societal diagnosis where developments in modern society alone are seen as generating loneliness (Schirmer and Michailakis, 2016). Regarding the issue of responsibility, elder-care is seen as focusing on all other factors affecting humans and not focusing on the social needs of older people.…”
Section: Resultsmentioning
confidence: 99%
“…Another finding from their study, which also touches on the issue of responsibility, was that older people were represented as forgotten by society and that elder-care was described as inhuman. In the study by Schirmer and Michailakis (2016), societal changes and the transition from traditional to modern societies was seen as causing an individualistic society with less fellowship, leading to an increase in loneliness.…”
Section: Introductionmentioning
confidence: 99%
“…As such, our findings are one of the first to highlight the social dimensions of loneliness and this emotion’s capacity to affect social life and norms. While many have highlighted the growing awareness of emotions’ intrinsic link with social life, studies addressing such questions on a group or cultural-level are considerably underrepresented ( Keltner and Haidt, 1999 ; Schirmer and Michailakis, 2016 ; Van Kleef, 2016 ). To the best of our understanding, the majority of studies on loneliness apply a medical or psychological perspective emphasizing on the associations of loneliness with physical or mental health.…”
Section: Discussionmentioning
confidence: 99%
“…In the materialistic surface of secular dominance, although religion may have confronted a declining node in power assumption, the role of religious congregations, preaching, and beliefs in societal moves at this stage cannot be ruled out in the study of social responsibility because millions of people are associated with religions (Schirmer & Michailakis, 2016). A previous study of 3,055 corporations of countries of Europe and Eastern Asia showed that CSR performance was influenced by Hofstede's Cultural dimensions and the tendency of socially responsible practices by corporations in European countries was ahead than those in East Asian countries (Thanetsunthorn, 2015).…”
Section: Further Discussionmentioning
confidence: 99%